2018
DOI: 10.1007/s40123-018-0155-5
|View full text |Cite
|
Sign up to set email alerts
|

The USER Study: A Chart Review of Patients Receiving a 0.2 µg/day Fluocinolone Acetonide Implant for Diabetic Macular Edema

Abstract: Introduction To determine anatomical, functional, and intraocular pressure (IOP) responses to diabetic macular edema (DME) treatments pre- and post-0.2 µg/day fluocinolone acetonide (FAc) implant administration compared with baseline and the preceding 3 years. Methods This was a retrospective, chart review, cohort study in four U.S. centers. Patients received the 0.2 µg/day FAc implant for the treatment of DME in at least one eye before January 1, 2016. DME treatments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
89
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 14 publications
14
89
3
Order By: Relevance
“…Data from clinical real-world studies have established the safety profile of the FAc intravitreal implant in patients with DME that persists or recurs despite treatment, and the current study revealed no new safety findings. Indeed, patients previously exposed to a course of corticosteroids appear to have fewer IOP elevations after FAc implantation than those who have not been exposed to prior course of corticosteroids, 20,21 and the IOP increases that were observed in this study are in line with previously reported findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Data from clinical real-world studies have established the safety profile of the FAc intravitreal implant in patients with DME that persists or recurs despite treatment, and the current study revealed no new safety findings. Indeed, patients previously exposed to a course of corticosteroids appear to have fewer IOP elevations after FAc implantation than those who have not been exposed to prior course of corticosteroids, 20,21 and the IOP increases that were observed in this study are in line with previously reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings of the USER study, in which the percentage of patients achieving a dry macula significantly increased after FAc implantation. 21 It should be noted, however, that the follow-up period in the USER study was longer than in the current study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The low-dose FAc implant was ultimately FDA-approved as it met the primary endpoint where 33% of patients gained 15 letters or more from their baseline best-corrected visual acuity (BCVA) at 3 years as opposed to 21% in the placebo group. Furthermore, in the US Retrospective Chart Review in Patients Receiving Iluvien (USER) clinical study, treatment with FAc showed that in 160 eyes, 63% of the eyes required no additional treatment for DME 19…”
Section: Introductionmentioning
confidence: 99%
“…Large real-world studies in Europe and the USA demonstrated a significant reduction in injection burden after receiving the FAc implant while maintaining or improving VA and optical coherence tomography (OCT) central subfield thickness (CSFT) 14 15. There are, however, little or no studies assessing its impact on patient visits and also practice resource utilisation (based on ophthalmic visits and injection burden) so we now examine these aspects in our clinical practice.…”
Section: Introductionmentioning
confidence: 99%